Pengaruh Kualitas Lingkungan dan Motivasi pada Kinerja Akademik Siswa SMA - Kusuma, Yudhistira; Kusuma, Hanson Endra; Tampubolon, Angela Christysonia; Aryanti, Tutin (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2018)
Environment (external factors) and user attributes (internal factors) affect the user's response to the environment. This study aims to uncover how the quality of the environment in high school as an external factor and student motivation as an internal factor affects the academic performance of the students. The research was conducted with qualitative and quantitative approach. Data were collected by survey using an online questionnaire. From the regression analysis, it was found that the dimensions of external factors of